Diagnosis and management of a rare case of ruptured sinus of Valsalva into the right atrium - Charan Reddy KV; Bhavesh Vajifdar; Pavan Kumar; Aniket Vazirani (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Sinus of Valsalva Aneurysm (SOVA) can arise from any of the three aortic sinuses. Aneurysm arising from the right coronary sinus, rupturing into the right atrium is extremely uncommon. SOVA's are seen more in males than females and in Asians than other ethnic groups. Majority of the cases are diagnosed during routine echocardiography and conventional angiography. However, with the availability of other advanced imaging techniques, such as cardiac Computed Tomography (CT) and Magnetic Resonance (MR) has not only improved the diagnosis but also its treatment. We report the case of a SOVA affecting the right coronary sinus and its subsequent management.